PEMBERDAYAAN MASYARAKAT DESA MANGAR MELALUI PEMAN PEMANFAATAN SUMBER DAYA ALAM LOKAL BERUPA ASAM MENJADI CEMILAN PERMEN ASAM - kknuaposko40, hafil-123 (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Nature is the habitat of living beings in carrying out daily life, whether for food, shelter, and so on. It is evident that there is a close relationship between nature and living beings, as nature is the most important ecosystem and the driving force of the environment. Humans, as the perfect creation endowed with intellect by the creator of nature, are able to utilize their intellect to drive the development of life. From nature, humans are closely related to their surrounding environment. This environment can be utilized by communities in the form of natural resources that can be managed and processed by the community itself, thus providing positive impacts for villages, such as in the village of Mangar. This village, located in the Telanakan sub-district of Pamekasan district, has a majority of its population engaged in farming, particularly seasonal crops (rice, tobacco, chili, and eggplant). Additionally, some of the community also benefits from other natural resources such as tamarind and fish paste, which are then marketed. The community empowerment of local natural resources is still preserved, although not many of the population participate in this. Therefore, through entrepreneurship training, it is hoped that the people of Mangar village will become more innovative in managing their natural resources, such as producing tamarind candies, which can certainly help improve the economy of Mangar village.